The Practices and Difficulties of Coaching Young Sport Training Participants at Bahr Dar University Sports Academy - Melese Ebabu Mossa; Yilkal Chale Getie (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2024)
This study examined the Bahir Dar University Sports Academy's techniques and environment that help young children play sports. The researchers conducted focus group talks with trainees and one-on-one interviews with many coaches and senior officials to attain this goal. Bahir Dar University's sports academy directors, trainers, and trainees were research participants on purpose. The investigation included a qualitative case study and data theme analysis. The study found that most survey respondents believed students' training experiences and time and effort allocation were crucial to talent development. Best practices show that most sports trainings are well-managed in terms of time and schedules, equipment, training resources, and well-equipped locations, and many have solid relationships with instructors-coaches. Training issues include a lack of transportation to and from the training center, a lack of timely supervision and support, especially for sports, practical skill training without theoretical and psychological academic sciences, and playing a few friendly matches with more advanced clubs. Participants strongly advocated for some coaches to work with players regularly, for training to be well-balanced and supported by academic sciences, psychological training, and other critical factors, for transportation, dietary guidelines, and sporting equipment and materials, and for friendly matches with similar-aged players.